INDONESIA INTERNATIONAL MASK FESTIVAL SEBAGAI SARANA KOMUNIKASI INTERNASIONAL KOTA SURAKARTA PADA TAHUN 2014-2015 - Halifa Haqqi, Hayu Trisnaningtyas, Setyasih Harini & (Transformasi, 2016)
This research aims to explain or describe about Indonesia International Mask Festival as aninternational means of communication Culture Surakarta city in 2014-2015. The theory used inthis research international communication in the perspective of the culturalistic. The researchmethodology used is the type of qualitative descriptive study. Data sources used are primary andsecondary data. Data collection techniques in the study using a study of the literature, interviewsand related documents. The data analysis techniques used over the dish data, data reduction,and with draw all of the conclusion or verification of data. In conclusion, this event support theefforts of international communications with the purpose of achievement of maintaining aclimate of peace, avoid misunderstandings, avoiding and resolvingconflicts increase international cooperation, as well as support the implementation of foreignpolicy for Indonesia in its efforts to fight for the achievement of national interests in thecountries participating in the event Indonesia International Mask Festival.Keywords: Indonesia International Mask Festival, International Communication, CulturalEvents.